Long-term effectiveness, adherence and safety of twice-yearly paliperidone-palmitate long acting-injectable in patients with schizophrenia in Europe: 2-year mirror-image data from the paliperdone-2 per year study (P2Y) - Manchado Perero, Sofía; Rodríguez Lorente, Ana; García-Pérez, Alba; Isidro García, Guillermo; Forcen-Muñoz, Luis Alberto; Ovejero García, Santiago; Sáez Povedano, Rocío; González-Galdámez, Ana Luisa; Mata Iturralde, Laura; Ramirez Bonilla, Mariluz; Fuentes-Pérez, Paloma; Ovejas-Catalán, Claudia; et al. (Frontiers in Psychiatry, 2025)
BackgroundLAIs with longer dosing intervals appear to be associated with improved clinical outcomes and added real-world benefits in the management of schizophrenia. Paliperidone palmitate six-monthly (PP6M) LAI provides the longest dosing interval, twice-yearly dosing, among all currently available LAIs. In clinical trials PP6M was found to be non-inferior in preventing relapses in patients with schizophrenia compared to the three monthly formulation (PP3M) though real world data remain limited. Therefore, the aim of this study was to evaluate the acceptability, effectiveness, and safety of PP6M in patients with schizophrenia in real world practice.MethodsData were derived from a naturalistic cohort of patients enrolled in the international, multicenter, prospective Paliperidone-2-per Year (P2Y) study. In this 2-year mirror-image study we compare the number of hospital admissions 1 year pre- and post-PP6M initiation as well as the CGI scores at baseline and the point of each PP6M administration. Discontinuation rates and reasons were also collected.ResultsA total of 201 patients (107 outpatients and 94 chronic long-stay inpatients) were included. The majority of patients had switched to PP6M from either PP3M (76%) or PP1M (19%) while the 3% switched from aripiprazole 1-monthly and the 2% from risperidone-LAI and zuclopenthixol-LAI. The mean CGI-Severity score significantly reduced from baseline to the second and third PP6M administrations in the global cohort (2.31 ± 0.14 vs. 3.23, p=0.001) as well as in both subgroups. Moreover, the number of hospital admissions decreased from 0.2 ± 0.04 1-year period before to 0.07 ± 0.02 1 year after PP6M initiation (p=0.001). Only 6%, (12 patients, 10 out- and 2 inpatients) discontinued treatment at 1 year of follow-up; Kaplan-Meier curves demonstrated significant differences in PP6M treatment discontinuation between out- and inpatients (p=0.012). The main reason for discontinuation was lack of adherence (5 patients) while only 1 patient stopped treatment due to tolerability issues (extrapyramidal side effects).ConclusionsThis is the first mirror-image study in patients with schizophrenia treated with PP6M in real-world settings showing very high treatment persistence, reduced hospital admissions compared to previous LAIs and no major safety concerns. Our findings suggest that six-monthly treatment with a long-acting antipsychotic may confer additional benefits in the management of schizophrenia. Nonetheless, we were unable to determine the precise changes in symptoms. Therefore, future studies are needed to truly establish the role of PP6M.